Chitosan-based strategies as eco-friendly solutions for controlling Brettanomyces bruxellensis contamination in wine production - Tedesco, Francesco; Biundo, Antonino; Caporusso, Antonio; Pisano, Isabella; Siesto, Gabriella; Pietrafesa, Rocchina; Abry, Chloé; Hervé, Alexandre; Falabella, Patrizia; Capece, Angela (Frontiers in Microbiology, 2025)
IntroductionThis study investigates the antimicrobial activity of chitosan against Brettanomyces bruxellensis, a wine spoilage yeast responsible for producing volatile phenols that lead to undesirable sensory defects commonly referred to as “Brett” character. The most widely used antimicrobial compound in oenology is sulphur dioxide (SO2), due to its broad spectrum of action, but growing consumer demand for reduced chemical additives and evidence of Brettanomyces spp. resistance to it, have encouraged different alternative strategies. Among these, chitosan has been accepted for the control of Brettanomyces yeasts.MethodsIn this study, some B. bruxellensis strains were treated with different types of chitosan: a commercial product (chitosan extracted from shrimp shells), a fungal origin chitosan approved for oenological use and an insect-derived chitosan, which is used for the first time in oenology as Brettanomyces control strategy. The effects on yeast cells were assessed through analysis of cell wall composition, flow cytometry to evaluate cell viability and membrane integrity, and optical and electronic microscopic observation.Results and discussionOur results indicated that all chitosan types effectively reduced the yeast population, with commercial and insect-derived chitosan demonstrating higher efficacy than oenological one. These findings highlight insect-based chitosan as a promising, sustainable alternative for microbial control in wine production. Furthermore, its use supports circular economy principles, offering an eco-friendly solution reducing reliance on conventional chemical preservatives like SO2, contributing to support the development of new preservation methods with reduced environmental impact in the food industry.